DEFINIÇÕES E CARACTERÍSTICAS PARA PROJETOS EM ALVENARIA ESTRUTURAL - Müller, Bruna de Freitas; Haas, Alessandra; Mohamad, Gihad; Machado, Diego Willian Nascimento; Rizzatti, Eduardo; Roman, Humberto Ramos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Structural masonry is a constructive system where the modular basic unit is the block, which together with the mortar form the walls, which are responsible for absorbing all the vertical and horizontal actions. This work presents the main guidelines for the specification and detailing of the structural elements, whose purpose is to produce technically streamlined constructions that are coherent with the structural masonry system, based on performance criteria. The design of a structural masonry building must go through stages such as preliminary study, adaptation of design and modulation, choice of block unit type and slab type, installations positioning, wall detailing, specification of finishes, frames, control of materials and structural components and, the definition of the compatibilized executive project. These steps are important for masonry construction, because lack of project and detailing can compromise the system and generate global problems in the construction. Therefore, the application of the principles of constructability and performance are important tools to guide engineering and architecture professionals in the execution of projects in structural masonry.